Synergistic Effect of Oxygen Vacancies and Ni Species on Tuning Selectivity of Ni/ZrO2 Catalyst for Hydrogenation of Maleic Anhydride into Succinic Anhydride and γ-Butyrolacetone - Lili Zhao; Jianghong Zhao; Tianjie Wu; Min Zhao; Wenjun Yan; Yin Zhang; Haitao Li; Yongzhao Wang; Tiancun Xiao; Yongxiang Zhao (Nanomaterials, 2019)
ZrO2 nanoparticles, ZrO2 (P) and ZrO2 (H), with different tetragonal phase contents, were prepared. ZrO2 (P) possessed higher tetragonal phase content than ZrO2 (H). Ni/ZrO2 catalysts (10% (w/w)), using ZrO2 (P) and ZrO2 (H) as supports, were prepared using an impregnation method, and were characterized using XRD, Raman, H2-TPR, XPS, and H2-TPD techniques. Their catalytic performance in maleic anhydride hydrogenation was tested. The Ni/ZrO2 (P) catalyst exhibited stronger metal-support interactions than the Ni/ZrO2 (H) catalyst because of its higher number of oxygen vacancies and the low-coordinated oxygen ions on its surface. Consequently, smaller Ni crystallites and a higher C=C hydrogenation activity for maleic anhydride to succinic anhydride were obtained over a Ni/ZrO2 (P) catalyst. However, the C=O hydrogenation activity of Ni/ZrO2 (P) catalyst was much lower than that of the Ni/ZrO2 (H) catalyst. A 43.5% yield of γ-butyrolacetone was obtained over the Ni/ZrO2 (H) catalyst at 210 °C and 5 MPa of H2 pressure, while the yield of γ-butyrolactone was only 2.8% over the Ni/ZrO2 (P) catalyst under the same reaction conditions. In situ FT-IR characterization demonstrated that the high C=O hydrogenation activity for the Ni/ZrO2 (H) catalyst could be attributed to the surface synergy between active metallic nickel species and relatively electron-deficient oxygen vacancies.